General Considerations for On-Animal Ectoparasiticidal Product Evaluations. Issue 6 (2nd November 2020) - Smythe, Brandon G; Sanchez-Sandoval, Ulises A
Abstract: Successfully preparing for and conducting on-animal ectoparasiticidal evaluations is key in providing accurate results and inferences on product performance. However, the procedures associated with designing sound-reliable research projects while using animal test subjects can become complex. The current manuscript offers insights towards the characterization of different evaluation types highlighting key considerations and potential problematic barriers that may otherwise be overlooked by researchers new to the area of on-animal product evaluation. Furthermore, recommendations on reporting inferences from findings based on various study designs are discussed. The authors of the current manuscript offer these considerations in the hopes of maintaining harmony in future reports used to develop and evaluate on-animal ectoparsiticidal products in the field of veterinary entomology.